The life history of a minnow, Barbus Anoplus, in a man-made lake in South Africa - Cambray, James Alfred (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1982)
Aspects of the life history strategy of Barbus anoplus Weber were studied in a turbid man-made lake (P.K. Ie Roux impoundment, Orange River system, South Africa). The minnow has successfully colonized the shoreline of the P.K. Ie Roux impoundment, where the preferred habitats of the chubbyhead barb are flooded stream beds, erosion gullies and flooded ruderal communities. B. anoplus reaches sexual maturity in one year, at a length of about 40mm FL. They have a multiple spawning habit, with the first spawn in November or December and the second spawn in February or March. A part of the adult population undertakes a spawning migration up inflowing tributaries, while the other part breeds along the shoreline. The eggs and young develop rapidly and a proportion of the protolarvae float near the water surface, where they are probably dispersed by water currents. Most of the males die off after their second summer, whereas many females live into a third summer. Females also attain a larger maximum size (73mm FL) than males (60mm FL). The importance of increasing the reproductive potential of B. anoplus by multiple spawning is discussed. Feeding studies indicate that B. anoplus are opportunistic predators on invertebrates. The feeding habits of minnows collected from four different habitats varied. Minnows collected in the open water fed mainly on zooplankton, while shoreline populations fed on chironomid larvae and zooplankton. The most varied diet was found in fish living in a well-vegetated tributary of the impoundment which was not subject to inundation. B. anoplus is basically an r-strategist (i.e. it is small in size, shortlived, males have bright colouration, high seasonal reproductive potential). These characteristics enable the species to colonize and successfully inhabit unstable environments and probably accounts for the fact that it is the most widespread species south of the Limpopo River system. It is recommended that B. anoplus be considered as a candidate in southern Africa for further studies on life history strategies.
Keywords: Minnows -- South Africa